Single-Dose Testosterone Administration Impairs Cognitive Reflection in Men. (October 2017) - Nave, Gideon; Nadler, Amos; Zava, David; Camerer, Colin
In nonhumans, the sex steroid testosterone regulates reproductive behaviors such as fighting between males and mating. In humans, correlational studies have linked testosterone with aggression and disorders associated with poor impulse control, but the neuropsychological processes at work are poorly understood. Building on a dual-process framework, we propose a mechanism underlying testosterone's behavioral effects in humans: reduction in cognitive reflection. In the largest study of behavioral effects of testosterone administration to date, 243 men received either testosterone or placebo and took the Cognitive Reflection Test (CRT), which estimates the capacity to override incorrect intuitive judgments with deliberate correct responses. Testosterone administration reduced CRT scores. The effect remained after we controlled for age, mood, math skills, whether participants believed they had received the placebo or testosterone, and the effects of 14 additional hormones, and it held for each of the CRT questions in isolation. Our findings suggest a mechanism underlying testosterone's diverse effects on humans' judgments and decision making and provide novel, clear, and testable predictions.